PENGEMBANGAN METODE COBLAS (Consulting Based Learning for ASEAN SMEs) UNTUK PENDIDIKAN KEWIRAUSAHAAN LANSIA DI USAHA KECIL MENENGAH (UKM) - Nurminingsih (Transpublika Publisher, 2023)
The purpose of this research is to develop the COBLAS (Consulting Based Learning for ASEAN SMEs) method as an innovative approach in teaching entrepreneurship to elderly groups in the Small and Medium Enterprises (SMEs) environment. The presence of older people in the business sector has potential that can be optimized with an appropriate learning approach. The COBLAS method, which has been successfully applied in supporting the development of SMEs in ASEAN countries, will be adapted and applied in the context of teaching entrepreneurship to the elderly in SMEs. This research adopts a descriptive qualitative approach with data collection methods through literature study, field observation, and interviews. Research participants included elderly SMEs and experts in education and entrepreneurship. The collected data were analyzed through the process of data reduction, data presentation, and verification. The results of this study provide an important contribution in the development of entrepreneurship learning methods that are in accordance with the characteristics and potential of the elderly in SMEs. The adaptation of the COBLAS method provide practical guidelines in designing effective and inclusive entrepreneurship teaching programs for the elderly in SMEs. As a result, this research has significant implications in maximizing the role and contribution of older adults in local economic development and sustainable development.